COVID-19 Vaccine Failure in a Patient with Multiple Sclerosis on Ocrelizumab - Sridhar Chilimuri; Nikhitha Mantri; Sudharsan Gongati; Maleeha Zahid; Haozhe Sun (Vaccines, 2021)
Vaccines will play a key role in ending the COVID-19 pandemic. Vaccination against infections remains an important part of the management of patients with multiple sclerosis. However, there are limited data about the safety and efficacy of the currently available COVID-19 mRNA vaccines in patients with multiple sclerosis receiving concurrent immunosuppressive therapies. Patients on B cell depleting therapy such as ocrelizumab have an attenuated vaccine response. We report the first case of COVID-19 vaccine failure in a patient with relapsing-remitting multiple sclerosis on B cell depleting therapy, ocrelizumab. We offer suggestions to improve vaccine efficacy in these patients.